2018
DOI: 10.1016/j.tranon.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

eEF1A1 Overexpression Enhances Tumor Progression and Indicates Poor Prognosis in Hepatocellular Carcinoma

Abstract: Liver is a major contributor of protein production physiologically. The aberrant state of protein synthesis leads to tumor progression. Eukaryotic elongation factor 1 alpha 1 (eEF1A1) is a major member of the eukaryotic elongation factor family that regulates protein synthesis. Although eEF1A1 plays an essential role in controlling the cell fate, its clinical significance in tumor development and progression has not been reported. Here, we aimed to uncover the expression and prognostic significance of eEF1A1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…In sharp contrast to reduced EEF1A1 mRNA expression, we observed that at the protein level, eEF1α1 is overexpressed in breast carcinomas, in particular in ER+, PR+ and lymph node-negative tumors. This is consistent with observations in hepatocellular carcinomas 48 , 49 . We also find that in breast cancer cell lines, eEF1α1 levels correlate with protein levels of HSP90α 1 and HSP90α 2 , which are markers of the heat shock response (HSR).…”
Section: Discussionsupporting
confidence: 93%
“…In sharp contrast to reduced EEF1A1 mRNA expression, we observed that at the protein level, eEF1α1 is overexpressed in breast carcinomas, in particular in ER+, PR+ and lymph node-negative tumors. This is consistent with observations in hepatocellular carcinomas 48 , 49 . We also find that in breast cancer cell lines, eEF1α1 levels correlate with protein levels of HSP90α 1 and HSP90α 2 , which are markers of the heat shock response (HSR).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have revealed that EEF1A is not only a translation factor but also involved in many non-canonical functions including oncogenesis, protein degradation, pro-apoptotic or anti-apoptotic activity, and cytoskeleton modulation [10,11,12,13]. Notably, many studies have shown that EEF1A is a prognostic factor for several solid tumors such as ovary [11,14], breast [15,16,17], lung [18], pancreas [19,20], stomach [21,22], prostate [23], and liver cancers [24,25]. Based on the previous results from the Wx neural network-based feature selection algorithm and those reporting the role of EEF1A1 in human solid cancer, we hypothesized that EEF1A1 is related to the prognosis of patients with colon adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…EEF1A1 is a well-known HCC biomarker and is considered one of the top 20 genes related to human hepatocarcinoma cell lines. EEF1A1 has been reported as a novel prognosis biomarkers for liver cancer using a multivariate analysis done in [55]. In our experiment, EEF1A1 was retrieved as a down-regulated gene with a significant p value, as illustrated by Figure 7.…”
Section: Discussing the Relevance Of Extracted Key Genes Based On Thementioning
confidence: 64%